Mabuting kaibigan...masamang kaaway (Manila Aquarius Records)
Your bestfriend can be your worst enemy. Armando Guevarra (Fernando Poe Jr.) and Ricardo Montinola (Vic Vargas) grew together, had their best childhood and almost breathe together. They were inseperable and nobody even dares to test their friendship. But Ric got blinded by his ambition and discard the so-called friendship. He will removed all the cobwebs and barriers just to get his goal, imagine how worst he is as enemy.
VCD
Produced by E.D.L., directed by Augusto Salvador
Fernando Poe, Jr., Vic Vargas, Marianne Dela Riva, Subas Herrero, Ali Sotto and Paguito Diaz
Keywords: Feature films--Phils.